2019
DOI: 10.1093/ptj/pzz111
|View full text |Cite
|
Sign up to set email alerts
|

Blinding Strategies in Dry Needling Trials: Systematic Review and Meta-Analysis

Abstract: Background Blinding of participants and therapists in trials of physical interventions is a significant and ongoing challenge. There is no widely accepted sham protocol for dry needling. Purpose The purpose of this review was to summarize the effectiveness and limitations of blinding strategies and types of shams that have been used in dry needling trials. Data Sources … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 73 publications
0
31
0
Order By: Relevance
“…Based on the current evidence, it seems that the application alone of dry needling targeting active TrP may be effective for the treatment of neck pain (low-to-moderate evidence); however, the effects were mostly observed at the short-term (2–12 weeks after treatment) and vs. sham/placebo/waiting list/other forms of dry needling but not against manual therapy or physical therapy interventions. In fact, the topic of a proper sham needling approach is questioned, since sham needling interventions used in the current literature are highly diverse, limiting the comparability of blinding effectiveness across current studies [ 52 ]. It has been supported that sham needling could also have a potential therapeutic effect, probably related to cognitive factors, such as expectative or placebo [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the current evidence, it seems that the application alone of dry needling targeting active TrP may be effective for the treatment of neck pain (low-to-moderate evidence); however, the effects were mostly observed at the short-term (2–12 weeks after treatment) and vs. sham/placebo/waiting list/other forms of dry needling but not against manual therapy or physical therapy interventions. In fact, the topic of a proper sham needling approach is questioned, since sham needling interventions used in the current literature are highly diverse, limiting the comparability of blinding effectiveness across current studies [ 52 ]. It has been supported that sham needling could also have a potential therapeutic effect, probably related to cognitive factors, such as expectative or placebo [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the topic of a proper sham needling approach is questioned, since sham needling interventions used in the current literature are highly diverse, limiting the comparability of blinding effectiveness across current studies [ 52 ]. It has been supported that sham needling could also have a potential therapeutic effect, probably related to cognitive factors, such as expectative or placebo [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…The topic of a proper sham needling intervention should also be considered, since it is not possible to determine that real dry needling is superior to sham dry needling. In fact, Braithwaite et al concluded that sham needling interventions used in clinical trials are diverse, limiting the comparability of blinding effectiveness across current studies [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Braithwaite et al concluded that sham needling approaches used in most studies investigating the effects of dry needling are highly heterogeneous limiting comparability of blinding effectiveness across published trials. 40 Development of proper sham needling interventions and proper blinding of patients during dry needling interventions are needed to further elucidate the true effects of dry needling. In fact, the potential role of patient expectations or previous beliefs in the effects of dry needling has been recently discussed in the literature.…”
Section: Discussionmentioning
confidence: 99%